Design of a 4-DOF grounded exoskeletal robot for shoulder and elbow rehabilitation - Karadeniz, Fatih; Aydoğan, Özgür Ege; Kazancı, Emin Abdullah; Akdogan, Erhan (Sustainable Engineering and Innovation, 2020)
The number of cerebrovascular and neuromuscular diseases is increasing in parallel with the rising average age of the world’s population. Since the shoulder anatomy is complex, the number of rehabilitation robots for shoulder movements is limited. This paper presents the mechanical design, control, and testing of 4 degrees of freedom (DOF) grounded upper limb exoskeletal robot. It is capable of four different therapeutic exercises (passive, active assistive, isotonic, and isometric). During the mechanical design, the forces to be exposed to the robot were determined and after the design, the system was tested with strength analysis. Also, a low-cost electromyograph device was developed and integrated into the system to measure muscular activation for feedback and instantaneously muscle activation control for the physiotherapist during the therapy. The system can be used for rehabilitation on the shoulder and elbow. A PID controller for position-controlled exercises was developed. The test results were presented in terms of simulation and the real system for passive exercise. According to the test results, the developed system can perform the passive exercise and can be used for other therapeutic exercises as well.